(untitled) (Cardiovascular Journal, 2020)
Certain congenital heart defects require the creation of an unrestrictive atrial septal defect (ASD) secundum to achieve adequate atrial mixing to improve systemic oxygen saturation by placing septal stent. We reported a case of 7-month-old child who was presented with shock like state with marked desaturation. He was diagnosed as a case of mixed total anomalous pulmonary venous return with restricted closing ASD secundum. We performed atrial septal stenting as a palliative procedure for saving the life. Creation or enlargement of ASD in infants using nonconventional transcatheter techniques is feasible, safe, and effective when usual technique fails or not suitable. After the procedure systemic saturation improved and patient became hemodynamically stable and there after rerouting of pulmonary veins to left atrium with ASD closure and removal of stent done by open heart surgery and send him home safely. Cardiovasc. j. 2020; 13(1): 86-91